Gang research in the Caribbean - Maguire, Edward R. (The Oxford handbook of gangs and society, 2024)
The Caribbean region is a well-known tourist destination due to its beaches and other attractions. Unfortunately, it is also home to a significant violent crime problem. Research has shown that much of the violence is due to criminal gangs. This chapter reviews the research on gangs in the Caribbean with a particular focus on the methodologies used to understand a variety of gang-related phenomena, including the nature and characteristics of gangs; gang membership; crime, violence, and conflict associated with gangs; and interventions intended to address these issues. The chapter concludes with a discussion about how the methodologies used to study gangs in the Caribbean have evolved, current gaps in theory and research, and recommendations for addressing these gaps.